Corynebacterium senegalense sp. nov. and Arthrobacter senegalensis sp. nov., two new Actinobacteria isolated from skin swab from the palm of hand. (September 2019) - Ndiaye, C.; Fall, N.S.; Kuete, E.; Lo, C.I.; Raoult, D.; Sokhna, C.; Lagier, J.-C.
Abstract: Corynebacterium senegalense strain Marseille-P4329 T (= CSURP4329) and Arthrobacter senegalensis strain Marseille-P4329 T (= CSURP4198) are new species first isolated from human skin. A culturomics approach and taxonogenomics methods were used for these new bacterial species.